Efektivitas Penanganan Gangguan Sistem melalui Incident Management Practice ITIL 4: Tinjauan Sistematis 15 Studi Kasus Organisasi di Indonesia - M. Irdan Aljibran; Muhammad Fadhil Ramadhan; Fenny Purwani (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
Information Technology (IT) service management is a fundamental pillar for supporting organizational operations in the digital era, across both public and private sectors. However, high dependence on IT is often not balanced with measurable governance, risking decreased service quality for users. This study aims to evaluate the maturity level of IT service management using the Information Technology Infrastructure Library (ITIL) framework as the primary audit instrument. The research method employed is a descriptive literature review and comparative analysis of 15 organizational case studies in Indonesia, encompassing government agencies, the hospitality sector, healthcare services, and commercial platforms. The results indicate significant variations in maturity levels; while a few educational organizations have reached level 4 (Managed), the majority of public and private services remain at level 3 (Defined) and level 2 (Repeatable). Key findings identify critical obstacles such as unsystematic incident management, manual helpdesk systems, high dependence on centralized servers in public services, and a lack of HR competence in implementing formal Standard Operating Procedures (SOP). This study’s contribution provides a map of current IT service maturity conditions and strategic recommendations for IT managers to standardize operational procedures and enhance staff capacity to ensure sustainable, high-quality, and measurable service in the future.